3, 4-Dibromo-7-Azaindole Modulates Arabidopsis Circadian Clock by Inhibiting Casein Kinase 1 Activity. (14th September 2019) - Ono, Azusa; Sato, Ayato; Fujimoto, Kazuhiro J; Matsuo, Hiromi; Yanai, Takeshi; Kinoshita, Toshinori; Nakamichi, Norihito
Abstract: The circadian clock is a timekeeping system for regulation of numerous biological daily rhythms. One characteristic of the circadian clock is that period length remains relatively constant in spite of environmental fluctuations, such as temperature change. Here, using the curated collection of in-house small molecule chemical library (ITbM chemical library), we show that small molecule 3, 4-dibromo-7-azaindole (B-AZ) lengthened the circadian period of Arabidopsis thaliana (Arabidopsis). B-AZ has not previously been reported to have any biological and biochemical activities. Target identification can elucidate the mode of action of small molecules, but we were unable to make a molecular probe of B-AZ for target identification. Instead, we performed other analysis, gene expression profiling that potentially reveals mode of action of molecules. Short-term treatment of B-AZ decreased the expression of four dawn- and morning-phased clock-associated genes, CIRCADIAN CLOCK-ASSOCIATED 1 ( CCA1 ), LATE ELONGATED HYPOCOTYL ( LHY ), PSEUDO-RESPONSE REGULATOR 9 ( PRR9 ) and PRR7 . Consistently, amounts of PRR5 and TIMING OF CAB EXPRESSION 1 (TOC1) proteins, transcriptional repressors of CCA1, LHY, PRR9 and PRR7 were increased upon B-AZ treatment. B-AZ inhibited Casein Kinase 1 family (CK1) that phosphorylates PRR5 and TOC1 for targeted degradation. A docking study and molecular dynamics simulation suggested that B-AZ interacts with the ATP-binding pocket of human CK1 delta, whose amino acid sequences are highly similar to those of Arabidopsis CK1. B-AZ-induced period-lengthening effect was attenuated in prr5 toc1 mutants. Collectively, this study provides a novel and simple structure CK1 inhibitor that modulates circadian clock via accumulation of PRR5 and TOC1.